Contralateral bone widening and transfer for limb sparing in a cat - Petazzoni, Massimo (Veterinary and Comparative Orthopaedics and Traumatology, 2016)
Objective: To report on a novel surgical procedure to treat a long segmental tibial defect in a five-year-old 5 kg spayed female Main Coon cat using transverse distraction osteogenesis in the contralateral tibia to create a free autograft.Methods: A long free bone segment was created from the cranial half of the normal tibia. A circular external fixator was constructed to give the segment 7 mm of cranial distraction. After 42 days the widened section of tibial bone was removed and transferred to the defect in the contralateral tibia. Locking plates were used to stabilize the graft and to protect the donor tibial sites.Results: By 27 months, both tibias were healed, all implants had been removed, function was excellent, and the overall limb length was 90% of the normal side.Clinical relevance: Compared with longitudinal distraction osteogenesis in long bone defects, transverse distraction of a normal bone requires a significantly shorter distraction distance to produce a similar amount of bone. Thus, distraction time is reduced, with less likelihood of significant soft tissue damage. New bone may be more reliably regenerated in a normal limb due to better tissue health, and native bone may be more readily incorporated than allografts in compromised sites. Disadvantages include the increased morbidity, as well as the risk and expense associated with involvement of a normal limb.
Keywords: Distraction osteogenesis; free cortical autograft; bone defects; circular external fixator; bone-widening